THE PERSONALITY AND TEACHINGS OF SYEKH SITI JENAR - Musda, Novelia (Universitas Islam Negeri Imam Bonjol Padang, 2014)
When we come across to the name Syekh Siti Jenar, our mind will turn to one of the most famous walis (Moslemmystics) in the history of Indonesia. Syekh Siti Jenar is famous both for ordinary people as well as intellectualscholars dealing with the history of Islam and mysticism in Indonesia. Some people doubt that this Syekh is reallya historical personality, but more people believe the existence of Syekh Siti Jenar is real. The life and teachingsof Syekh Siti Jenar as exposed by many books immediately remind us of those of the martyr Sufi al-Hallâj(244-309 H/857-922 AD). There is striking similarity between two personalities despite many differences. Itis suggested that the written sources seem to make easy and simple the doctrine of Siti Jenar and even said thatthe mystical teachings of him are clear and open to everyone; while in fact, they are not.